Barriers to Collaborative Innovation: Arabic Teachers' Reluctance to Share Teaching Methods - Khalid, Fakhrirozin; Setiyawan, Agung (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
There is an increasing need for Arabic teaching resource innovations. However, innovations developed by teachers remain less prominent compared to those developed by researchers, despite the teachers' advantage of interacting directly with students. The aim of this research is to analyze demotivating factors for Arabic teachers’ to share their teaching methods. This research is a quantitative study with linear regression method to analyze data acquired from 30 highschool’s Arabic language teachers in Yogyakarta. The results show that the factors with the lowest average scores are teacher busyness and personal comfort. Linear regression analysis reveals that unilateral decision-making by school principals, without considering teachers' input, significantly affects teachers' motivation to participate in activities requiring them to share their teaching methods. The p-value for variable X is 0.008, which is less than 0.05, confirming that autocratic leadership significantly contributes to teachers’ demotivation. The F significance value is also below 0.05, indicating that the regression analysis is statistically significant. This finding presses the necessity to reevaluate teachers’ collaboration in the field and form ways to empower teachers' innovations.